The Powdered Red Macroalgae (Eucheuma spinosum) Supplementation Potentially Enhanced Bone Structure in Osteoporotic Mice - Jusniar Patandung; Ika Yustisia; Rosdiana Natzir; Gita Vita Soraya; Lia Hafiyani; Sulfahri Sulfahri (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Red macroalgae, such as Eucheuma spinosum, have been found to have potential benefits for bone health due to their unique bioactive compounds, including proteins, polyphenols, polysaccharides, vitamins, and minerals. Therefore, this study was conducted to evaluate the benefits of powdered E. spinosum supplementation in osteoporosis-induced mice.METHODS: Thirty middle-aged mice were divided into 6 groups, namely: healthy control group (HC), negative control group (NC), positive control group (PC), and treatment groups supplemented with 1.25 mg/gBW (T1), 2.5 mg/gBW (T2), and 5 mg/gBW (T3) of E. spinosum powder for twenty days. Mice in NC, PC, T1, T2, and T3 groups were induced with 0.0029 mg/gBW of dexamethasone for 30 days to create osteoporosis mice models. Alkaline phosphatase (ALP) levels were measured by colorimetric methods before and after the intervention. Bone structures were evaluated using X-ray images and histological examination.RESULTS: After the intervention, PC, T1, T2, and T3 groups showed a significant decrease (p≤0.01) in serum ALP levels compared to the NC group, which experienced an increase in ALP levels. The X-ray images revealed that the PC, T1, T2, and T3 showed radiopaque bone density. For bone histology, PC, T2, and T3 showed an improvement with thickened and intact trabeculae, but T1 still had visible osteoporosis cavities.CONCLUSION: Supplementation of 2.5 and 5 mg/gBW of E. spinosum powder were able to improve bone density as well bone histology. Therefore, E. spinosum powder supplementation might potentially improve bone structure in osteoporosis.KEYWORDS: Eucheuma spinosum, red macroalgae, alkaline phosphatase, osteoporosis